Teaching Girls About Puberty and Menstrual Hygiene Management in Rural Ethiopia: Findings From a Pilot Evaluation. Issue 5 (September 2018) - Blake, Sarah; Boone, Melissa; Yenew Kassa, Alene; Sommer, Marni
Educational interventions on menstruation and puberty have emerged as an important element of efforts to improve girls' knowledge and confidence related to puberty, menstruation, and menstrual hygiene management (MHM). We conducted a mixed-methods evaluation of the Ethiopia Growth and Changes puberty book, developed through research with Ethiopian girls to present scientifically accurate content on MHM in a format appropriate to girls' lives. Deploying a cluster-randomized approach, we conducted quantitative surveys with girls enrolled in Grades 6 and 7 ( n = 636) in 10 intervention and 10 control schools in two rural districts of the West Shewa Zone of Oromia, Ethiopia. We collected qualitative data from girls in intervention schools. We found that the book was associated with a statistically significant improvement in knowledge, and evidence of improvements in attitudes around menstruation. Qualitative evidence underscored a strong interest in interventions that present information on menstruation and puberty in accurate and supportive terms. Consistent with an ecological framework for adolescent health, we conclude that puberty books offer a useful individual-level intervention, whose impact would be magnified if combined with investments aimed at creating more gender equitable physical and social school environments.